2008
DOI: 10.1016/j.geoderma.2008.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian calibration of the VSD soil acidification model using European forest monitoring data

Abstract: Over the past years, Bayesian calibration methods have been successfully applied to calibrate ecosystem models. Bayesian methods combine prior probability distributions of model parameters, based on assumptions about their magnitude and uncertainty, with estimates of the likelihood of the simulation results by comparison with observed values. Bayesian methods also quantify the uncertainty in the updated posterior parameters, which can be used to perform an analysis of model output uncertainty. In this paper, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 28 publications
1
39
0
1
Order By: Relevance
“…PBMs are more commonly parameterised site-specifically, even when multiple sites are examined in the same study (e.g. Lehuger et al 2009, but see Reinds et al 2008 Fig. 4 Yields (g m -2 ) for each of the six within-rotation harvests, averaged over all three-year long rotations that were simulated (1995-1997, 1998-2000, ..., 2010-2012).…”
Section: Bayesian Calibration Of a Pbm For Different Cultivarsmentioning
confidence: 99%
“…PBMs are more commonly parameterised site-specifically, even when multiple sites are examined in the same study (e.g. Lehuger et al 2009, but see Reinds et al 2008 Fig. 4 Yields (g m -2 ) for each of the six within-rotation harvests, averaged over all three-year long rotations that were simulated (1995-1997, 1998-2000, ..., 2010-2012).…”
Section: Bayesian Calibration Of a Pbm For Different Cultivarsmentioning
confidence: 99%
“…Further information about data acquisition can be derived from Conrad and Fohrer (2009b). Observed soil solution concentrations can vary considerably, and measurement uncertainty is affected most likely by the spatial variability within the plot (Reinds et al, 2008). De Vries et al (1999 reported a spatial variability of measured soil solution concentrations between 20-60% depending on depth and type of ion in forest soils from the Netherlands.…”
Section: Site Description and Measurementsmentioning
confidence: 99%
“…De Vries et al (1999 reported a spatial variability of measured soil solution concentrations between 20-60% depending on depth and type of ion in forest soils from the Netherlands. In Reinds et al (2008), an uncertainty of 30% was used for major ions at 40-60 cm depth for the Dutch forest plots. For low concentrations that are often measured for NO 3 or aluminium, the measurement uncertainty is probably higher than 30%.…”
Section: Site Description and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations